Toward subtalar joint axis–driven computer-aided design and computer-aided manufacturing foot orthoses: Reliability of a noninvasive clinical scanning protocol. - Potier, Clément; Claeys, Kurt; Deschamps, Kevin (Prosthetics & Orthotics International, 2025)
Background: The subtalar joint axis (STJA) occupies a key role in the dynamics of the lower limb kinetic chain, and its location has a wide interindividual variability. It has been suggested that considering the STJA location when designing foot orthoses may help to apply the required mechanical dose. However, the evidence is more anecdotal than empirical. Objective: This study aimed to evaluate the reliability of the STJA digitization, a procedure combining the clinical determination of the functional STJA location and its subsequent 3-dimensional (3D) scanning. Study Design: Two examiners identified the posterior and anterior exit points of the functional STJA on the skin of 15 healthy participants using a clinical method in a repeated-measure design. Methods: A handheld 3D scanner was used to scan the feet and the skin markers. The 3D coordinates of the skin markers were subsequently quantified and (1) STJA digitization intratester within-session, (2) STJA digitization intratester between-session, and (3) STJA digitization intertester between-session reliabilities were evaluated. Results: When pooling all skin marker 3D coordinates, intraclass correlation coefficients (ICCs) for the STJA intratester within-session reliability ranged from 0.74 to 0.98. ICCs for the STJA digitization intratester between-session reliability ranged from 0.58 to 0.94. ICCs for the STJA digitization intertester reliability ranged from 0.56 to 0.81. Standard error of measurement for the mediolateral position of the talus marker (anterior exit point of the STJA) was substantially higher than that for the other coordinates. Conclusions: Overall, the STJA digitization demonstrated a good intratester between-session reliability and may be used in a computer-aided design and computer-aided manufacturing workflow to create foot orthoses. However, further efforts should be considered to improve the scanning process and intertester reliability.